Letting a Picture Speak a Thousand Words: Arts-based Research in a Study of the Careers of Female Academics. (February 2023) - Sharafizad, Fleur; Brown, Kerry; Jogulu, Uma; Omari, Maryam
This article presents an adaptation of an arts-based research method usually reserved for child-focused research to examine organizational processes. We developed Draw, Write, Reflect (DWR), advancing a known method, Draw and Write, for investigating phenomena relating to child participants, to explore a new context: adults engaging in academic careers. This article reports on the rationale behind the novel use of this research method, outlines a DWR procedure for future research, and contains reflections of both the researchers and the respondents regarding their experiences participating in DWR. Offering participants a combination of visual and oral methods allowed the researchers to obtain data in a more individualized approach steered by participants' preferences. The multidimensional insights obtained through DWR would not have been attainable through each method on its own. Furthermore, we argue arts-based research can serve as a vehicle for disseminating academic work beyond conventional academe to a growing, nonacademic audience.